2020
DOI: 10.3168/jds.2020-19047
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the functional performance of industrial low-moisture part-skim mozzarella over a 1.5-year period

Abstract: Seventy-five blocks of low-moisture part-skim (LMPS) Mozzarella cheese were procured from an industrial cheese plant, and the relationships between the physicochemical and functional properties were evaluated during refrigerated storage. In total, cheeses were obtained from 1 cheese vat on 7 different production dates, at two-to four monthly intervals, over a 1.5 year period; all cheeses were made using a standard recipe. The cheeses were held at 4°C for 0, 1, 2, 4, 8, 16 or 32 d and assayed for composition, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
3
7
1
Order By: Relevance
“…2) resulted in decreases in the mean firmness (P < 0.001), springiness (P < 0.05) and cohesiveness (P < 0.001; not shown) of the cheese. This trend differs from that reported by To et al (2020a) for commercial LMPS Mozzarella cheeses, which showed no change in the mean firmness over a 32 d storage period. As the gross compositions of cheeses from both of these studies were similar, the observed inter-study differences in cheese firmness during storage at 4 °C may reflect the longer storage time duration, and consequently the higher level of pH4.6SN in the current study, i.e., ~ 6.7 vs 5.0% total N. It is well known that the firmness of Mozzarella and other cheeses correlates inversely with the degree of primary proteolysis (Creamer, Zoerb, Olson & Richardson, 1982;Feeney et al, 2001;Guinee et al, 2001).…”
Section: Functional Properties Of the Unheated Cheesecontrasting
confidence: 99%
See 3 more Smart Citations
“…2) resulted in decreases in the mean firmness (P < 0.001), springiness (P < 0.05) and cohesiveness (P < 0.001; not shown) of the cheese. This trend differs from that reported by To et al (2020a) for commercial LMPS Mozzarella cheeses, which showed no change in the mean firmness over a 32 d storage period. As the gross compositions of cheeses from both of these studies were similar, the observed inter-study differences in cheese firmness during storage at 4 °C may reflect the longer storage time duration, and consequently the higher level of pH4.6SN in the current study, i.e., ~ 6.7 vs 5.0% total N. It is well known that the firmness of Mozzarella and other cheeses correlates inversely with the degree of primary proteolysis (Creamer, Zoerb, Olson & Richardson, 1982;Feeney et al, 2001;Guinee et al, 2001).…”
Section: Functional Properties Of the Unheated Cheesecontrasting
confidence: 99%
“…This trend is analogous to that reported by O'Mahony, McSweeney & Lucey (2006) who found that increasing the insoluble Ca content of 4 month-old Cheddar cheese from 14 to 24 mg g -1 (by immersion of slices in buffers fortified to different concentrations of calcium chloride dehydrate) coincided with increases in firmness and fracture stress and reduction in LTmax on heating from 10 to 90 °C. The relatively minor effect of insoluble Ca on the functionality after the shorter storage periods (i.e., 14 or 56 d) concurs with findings of To et al (2020a) for commercial LMPS Mozzarella cheeses stored for 32 d at 4 °C and suggests that the weighted effects of different biochemical parameters on functionality are likely to vary with storage time.…”
Section: Relationships Between Biochemical and Functional Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…Understanding the relationships between cheese composition and storage-related changes in biochemical parameters facilitates the development of cheese with the desired functional attributes after a given storage period (Smith, Hindmarsh, Carr, Golding & Reid, 2017;To et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%